A Rare Sellar Lesion: Pituitary Actinomyces Infection - Yapar, Burcu; Ozdemir, Kevser; Kutlu, Murat; Civlan, Serkan; Kocaoglu, Murat; Baykara, Eyup; Celiker, Ozkan; Yalcın, Nagihan; Ozdemir, Mevci; Acar, Feridun; Ardıç, Necdet (Journal of Brain And Spinal Cancer, 2015)
Pituitary abscess is extremely rare and often misdiagnosed as pituitary tumor pre-operatively. We document a case of a 64-year-old lady presented to the outpatient department with complaints of headache and blurring vision of right eye for one month. Based on preliminary investigations, a clinical diagnosis of pituitary adenoma was made and the pituitary gland was surgically excised. Histopathological examination showed Actinomyces infection. This case has been documented due to the extremely rare involvement of the pituitary gland by actinomyces infection. Pituitary abscess is a rare pathology, but it must be considered during evaluating sellar masses, since its prognosis depends on surgical drainage and on the use of specific antibiotics. We report, to our knowledge, the fourth case of Actinomyces israelii infection of the pituitary region.
Keywords: Actinomyces israelii; pituitary abscess; transsphenoidal surgery; anti-microbial therapy